(3GdESJKeGQ hGdJehjd, GdJMdjd GdeGdj, GdCShGb GdeGdjI GdOhdjIs - (3eMeO SYjO(B, (3YHO GdgGOjs ((3YeGf(B:s (3OGQ MeO(B,s, 2008)
(3GdGOGQI GdeGdjI, GdGOGQI GdeGdjI hGdJNWjW GdeGdj ddeTQhY, GdbjeI GdRefjI ddfbhO, GdbhGFe GdeGdjI, GdJMdjd GdeGdj, JMdjd GdbhGFe GdeGdjI, GdJMdjd HGdeDTQGJ(B((3GdfSH(B) (3GdeGdjI, GdGSJKeGQGJ aj GdCUhd GdeGOjI, GdGSJKeGQ aj GdChQGb GdeGdjI, JNWjW GdGSJKeGQGJ aj GdGhQGb GdeGdjI, Jbjje GdGSJKeGQ, GOGQI hJNWjW GdeNRhf GdSdYjs
(3HHdjhZQGajG(B: (3U(B.295(3; edGMb(B: (3U(B.305(3; cTGa(B: (3U(B.291s
Keywords: (3GdChQGb GdeGdjIs; (3GdGOGQI GdeGdjIs; (3GdGSJKeGQs; (3GdJehjds